HUBUNGAN KESIAPAN BELAJAR MATEMATIKA SISWA DENGAN HASIL BELAJAR PADA MATERI BANGUN DATAR - Mohamad Syafii; Yayah Fauziyah (IKIP Siliwangi, 2022)
The aim of this paper is to find out empirically the relationship between readiness to learn mathematics and mathematics learning achievement in grade VII MTs Al-Masthuriyah Jakamulya, South Bekasi. This study uses a descriptive method with a survey technique in the form of a correlation study. The sample was taken from class VII-3 consisting of 34 students with purposive sampling technique. The research results obtained indicate that there is a positive relationship or correlation between learning readiness and mathematics learning achievement. This can be shown by the correlation coefficient rxyÂ = 0,863 and the regression equation Â 3,11+1,02x is obtained. The coefficient of determination shows that r2= (0,863)2=0,7448, which means that the contribution of the influence given to the learning readiness variable on the learning outcome variable in mathematics is 74.48%. The conclusion of this study is that there is a positive relationship between students' readiness to learn mathematics and learning outcomes in the chapter related to rectangular shapes for 7th grade students of MTs Al-Masthuriyah Bekasi Selatan.